Large Rhinophyma Treated by Surgical Excision and Electrocautery - Nabeel K. Al Hamzawi; Salih M. Al Baaj (Case Reports in Surgery)
Rhinophyma is a benign condition characterized by a large, bulbous nose with prominent pores. It is commonly associated with untreated cases of rosacea. The disease can carry a substantial psychological impact that causes patients to seek advice about how to improve their physical appearance. Many treatment options are available for rhinophyma, but there is no standard treatment protocol. Here, we describe the case of a 65-year-old man with a large rhinophyma that caused him cosmetic and psychosocial embarrassment. The condition was treated by surgical excision and bipolar electrocautery. No complications occurred after the procedures, and healing was completed 2 weeks later by secondary intention and reepithelialization. A simple surgical removal using a scalpel to shave off the abnormal tissue with electrocauterization of the bleeding points can be considered as a good treatment option for rhinophyma, as it results in an excellent cosmetic outcome and has short recovery time.